Designing Some Skill Tests According to Individual Offensive and Defensive Performance in Volleyball Players Aged 16 – 18 Years Old - Hussein, Shatha; Nuruddin, Samah (Journal of Physical Education, 2019)
The importance of the research lies in designing tests for some artistic skills according to offensive and defensive performance of volleyball players aged 16 – 18 years old. The research aimed at designing skill tests according to offensive and defensive performance of volleyball players aged 16 – 18 years old. The researchers used the descriptive method on (74) youth Iraqi Volleyball league. The data was collected and treated using proper statistical operations to conclude that the rests are able to distinguish among individuals of high and low level in one tests and that the tests understudy hare reliable valid and objective.